5a times 3a minus 8a = (5*3)*a2 - 8a = 15a2 - 8a
5a × 3a - 8a = 15a² - 8a = (15a - 8)a
-8a + 3a = (-8 + 3)a = (5)a = 5a
6b+5a-4b+3a= ? Rearrange it as 5a+3a+6b-4b = 8a+2b
5a + 4b - 3a =(5a - 3a) + 4b =2a + 4b =2 (a + 2b)
So we have 5a + 11 + 3a - 7 = -4 Start by combining common terms such as the 5a and 3a to give you 8a and 11 and -7 to give you 4. So now your equation is 8a + 4 = -4. Subtract 4 from both sides gives you 8a = -8. Divide -8 by 8 to give you a = -1, your solution.
Well if you are adding you would have 8a+2b subtract you would have -2a+2b
what is 5a x 3 x 2b
Since they are like terms, 5a*3a=15a. Find out what "a" is equal to and multiply it by 15. Then, and only then, will you get your answer.
2a + 3a = 5a
If your referring to addition, then it would be 8a+14b. If your multiplying it would be, 15a*24b simplified to 360ab.
3a x 2a =24